Emotion recognition in music changes across the adult life span - César F. Lima (2011)
In comparison with other modalities, the recognition of emotion in music has received little attention. An unexplored question is whether and how emotion recognition in music changes as a function of ageing. In the present study, healthy adults aged between 17 and 84 years (N=114) judged the magnitude to which a set of musical excerpts (Vieillard et al., 2008) expressed happiness, peacefulness, sadness and fear/threat. The results revealed emotion-specific age-related changes: advancing age was associated with a gradual decrease in responsiveness to sad and scary music from middle age onwards, whereas the recognition of happiness and peacefulness, both positive emotional qualities, remained stable from young adulthood to older age. Additionally, the number of years of music training was associated with more accurate categorisation of the musical emotions examined here. We argue that these findings are consistent with two accounts on how ageing might influence the recognition of emotions: motivational changes towards positivity and, to a lesser extent, selective neuropsychological decline.